Evolutionary history and divine presence - Rolston, Holmes, 1932-2025, author; Theology Today, publisher (Colorado State University. Libraries, 1998)
The genesis of life is keyed to genes evolving in organisms. There is remarkable debate about randomness and probability, the inevitable and the contingent, actualities and possibilities, as these result in increasing diversity and complexity. The generated biological information displays a cumulative creativity that, described by science, is nowhere implied by biological theory. Such genesis invites an account of God as the Ground of Information.
Keywords: evolution; Spirit of God; biology; secret of life; diversity; natural selection; complexity